Formal and Informal Mentoring: Complementary, Compensatory, or Consistent?. (March 2014) - Desimone, Laura M.; Hochberg, Eric D.; Porter, Andrew C.; Polikoff, Morgan S.; Schwartz, Robert; Johnson, L. Joy
Informal mentors likely play a substantial role in novice teacher learning, yet we know little about them, especially in relation to formal mentoring, which is the cornerstone to most induction programs. This study analyzes survey and interview data from 57 first-year mathematics teachers from 11 districts to investigate differences in the characteristics of formal and informal mentoring that can inform improvements in mentoring policy. Our findings suggest that informal and formal mentors sometimes serve similar functions but often provide compensatory and complementary support. Based on these findings, we identify a set of policy recommendations to improve new teacher supports.